2020
DOI: 10.1038/s42004-020-0304-3
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed fluoro-carbonylation of aryl, vinyl, and heteroaryl iodides using 2-(difluoromethoxy)-5-nitropyridine

Abstract: Acyl fluorides have recently gained a lot of attention as robust and versatile synthetic tools in synthetic chemistry. While several synthetic routes to acyl fluorides have been reported, a procedure involving direct insertion of the “fluoro-carbonyl” moiety using a single reagent has not yet been realized. Here we report the preparation of acyl fluorides by palladium-catalyzed fluoro-carbonylation of aryl, vinyl, and heteroaryl iodides using 2-(difluoromethoxy)-5-nitropyridine under CO-free conditions. 2-(dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The formation of amide bonds from the reaction of acyl halides and amines is one of the most atom-efficient pathways and therefore produces minimal waste in relation to the method mediated by activators. Although acyl chlorides are the most common acyl halides for amidation reactions, the use of acyl fluorides has recently attracted attention because of their stability and facile operation. The reaction between acyl fluorides and amines is typically performed in the presence of a base in a solvent. During the optimization of the conditions for the reaction of acyl fluoride 2a and n -butyl amine ( 3a ) to afford amide 4aa , we observed that mechanochemical coupling proceeded smoothly to afford 4aa in 93% yield without any base or solvent (Scheme B). This outcome was similar to that obtained in the presence of Et 3 N (2.0 equiv), yielding 4aa in a 94% yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The formation of amide bonds from the reaction of acyl halides and amines is one of the most atom-efficient pathways and therefore produces minimal waste in relation to the method mediated by activators. Although acyl chlorides are the most common acyl halides for amidation reactions, the use of acyl fluorides has recently attracted attention because of their stability and facile operation. The reaction between acyl fluorides and amines is typically performed in the presence of a base in a solvent. During the optimization of the conditions for the reaction of acyl fluoride 2a and n -butyl amine ( 3a ) to afford amide 4aa , we observed that mechanochemical coupling proceeded smoothly to afford 4aa in 93% yield without any base or solvent (Scheme B). This outcome was similar to that obtained in the presence of Et 3 N (2.0 equiv), yielding 4aa in a 94% yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…4A, eqn (2)). 27 It is likely that β-fluorine elimination of the weakly bound trifluoromethoxy group generates fluorophosgene which might bind to the palladium metal center, followed by insertion of the fluorophosgene into the Pd–Ar bond and a second β-fluorine elimination to give the corresponding acid fluoride.…”
Section: Resultsmentioning
confidence: 99%
“…7). 27 Considering the Pd(0) complex that could be generated after reductive elimination from Pd( ii ) complex, we also tried the thermal reaction of complex 5a in the presence of 10.0 equivalents of 1-bromo-(4- tert butyl)benzene or 3.0 equivalents of t BuBrettPhos. Again, the formation of the desired Ar–OCF 3 reductive elimination was not observed (Scheme 1, entry 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has developed various efficient methodologies for the electrophilic [14,15], nucleophilic [16], and radical [17] trifluoromethylation reactions for more than a decade. In recent years, we also reported the direct introduction of an acyl fluoride unit into aromatic compounds by the Pd-catalyzed cross-coupling reaction of aryl, vinyl, and heteroaryl iodides with 2-(difluoromethoxy)-5-nitropyridine [18]. A wide variety of acyl fluorides were efficiently obtained in high yields.…”
Section: Introductionmentioning
confidence: 99%